Learning for children in an educational enrichment: a perspective derived from Taiwan's Early Childhood Education & Care Curriculum Framework - Shih, Yi-Huang (Frontiers in Education, 2024)
Anchored in the educational philosophy of "benevolence," the Taiwan's Early Childhood Education & Care Curriculum Framework establishes nine learning goals and emphasizes the cultivation of six core competencies in young children.Recognizing that young children have potential for development, imagination, and creativity, the framework encourages young learners to engage with their surroundings, exhibit curiosity, and explore through play. The curriculum framework highlights the multifaceted roles of teachers, including their roles in shaping class culture and learning environments, partnering in the lives and learning journeys of children, guiding in their educational development, and collaborating with families. This curriculum framework emphasizes a child-centered approach to course development, integrating diverse activities that are reflective of and relevant to children's life experiences. It prioritizes maintaining the physical and mental health and safety of young children and introduces them to the meaning of life and the phenomenon of multiculturalism. The type of this study is a conceptual analysis, and it is a study from a reflective model on the implementation of the curriculum in Taiwan. Through this curriculum framework, children are encouraged to appreciate life's beauty and interact with others effectively and empathetically. Therefore, the curriculum framework emphasizes life education, multicultural education, aesthetic education, and moral education as essential components in the holistic development of young children. The curriculum framework is an educational enrichment for children's learning. This study explores the concept of early childhood learning as conceptualized by Taiwan's Early Childhood Education & Care Curriculum Framework.It is hoped that such an exploration can broaden young children's learning horizons, and enhance the quality of early childhood education.